Studies on evaluation of different Eucalyptus tereticornis Sm. clones - Kumar, Rakesh; Bangarwa, K.S.; Deswal, A.K. (Indian Journal of Agroforestry, 2020)
The present investigation was carried out to obtain information on comparative growth performance of Eucalyptus tereticornis clones with respect to growth attributes and their increments. Significant clonal differences were observed for all growth characters and their increments. Clone number 3 achieved the highest total height, clearbole height, unforked height whereas, clone number 71 recorded the maximum diameter at breast height. Significantly higher values for current annual increment of total height, clearbole height, unforked height and mean annual increment of diameter at breast height were also recorded by clone number 71. Clone number 3 recorded maximum mean annual increments for total height, clearbole height and unforked height.